È possibile una gestione "ideale" della pandemia da malattia renale cronica? - Stefano Michelassi (AboutScience Srl, 2022)
Chronic Kidney Disease (CKD) is recognized as one of the major categories of noncommunicable epidemic diseases and in the last decades it has been largely growing in incidence and prevalence all over the world. Ideal management of CKD pandemic should be comprehensive of measures of tertiary, secondary, primary and primordial prevention. So, it should include prompt diagnosis and treatment of traditional and non-traditional risk factors for CKD, optimal conservative treatment for non-dialysis dependent CKD patients and appropriated dialysis therapy or renal transplantation for patients with end-stage renal disease. However, these goals are not easy to obtain on a global scale. It would be possible only by a broad and holistic approach, ranging from good governance to achievement of the sustainable development goals (SDGs).